建立高等教育「教與學的學術」文化： 借鏡國際經驗展望臺灣教學實踐研究的推動 Establishment of Scholarship of Teaching and Learning Culture in Higher Education: Using International Experience to Examine the Promotion and Development of Taiwan's Teaching Practice Research - 符碧真 Bih-Jen Fwu; 李紋霞 Jennifer Wen-Shya Lee (National Taiwan Normal University, 2020)
自從 1990 年 Boyer 大聲疾呼教學的學術起，北美推展「教與學的學術」（Scholarship of Teaching and Learning, SoTL）迄今剛好滿 30 年。相對而言，臺灣推動教學實踐研究才剛起步，他山之石對我國發展 SoTL 校園文化頗具參考價值。本研究探討三個問題：一、SoTL 的本質為何？二、SoTL有哪些相關的論辯？三、我國 SoTL的推動與發展情形如何？文獻綜合指出，SoTL 的本質是教師從教學實務中找到問題意識，系統性地蒐集課程教學改進的資料，經學術 社群嚴格檢驗後，公開發表研究結果的探究活動。在推動 SoTL過程中，產生了 SoTL的目的、SoTL在教師升等機制中的定位、SoTL與教育研究的差別等論辯。本研究提出一個 SoTL校園發展狀況整合性分析框架，並對三所大學進行實徵研究。研究結果發現，各校園大部分的 SoTL文化發展處於教師微觀文化剛萌芽、機構支持建置成熟的階段，且在微觀－中觀－宏觀－巨觀等四層級的推動上有共通之處。最後針對發展 SoTL校園文化、推動教學實踐研究計畫等核 心議題提出評析與建議。 Since Boyer's original call to recognize the scholarship of teaching, the scholarship of teaching and learning (SoTL) movement has been popular in North American higher education for the last 30 years. Taiwan's promotion of research on teaching and learning practice is in its infancy. The lessons learned from North America are critical for the development of SoTL culture on university campuses in Taiwan. This article explored three questions: (1) What is the nature of SoTL? (2) What are the major issues in the development of SoTL? (3) How can SoTL be promoted and developed in Taiwan's higher education? SoTL refers to systematic inquiry activities such as identifying problems in teaching practices, collecting data to evaluate the results of teaching interventions, and publishing the results after peer review. The process of establishing SoTL has attracted several heated debates concerning aspects such as the purpose of SoTL research, the positioning of SoTL in faculty reward mechanisms such as tenure extension and promotion, and the differences between SoTL research and educational research. To investigate the current development of SoTL in Taiwan, this paper first proposed an integrated framework for analyzing the SoTL campus culture, after which an empirical study was conducted at three Taiwanese universities. The results indicated that the development of SoTL culture in the sample university campuses is at the stage of emerging microcultures with well-established institutional support. Moreover, the three universities shared some commonalities in the promotion of SoTL culture at the micro, meso, macro, and mega levels. On the basis of the empirical findings, the paper comments on the current development of SoTL and offers suggestions for further promotion of teaching practice research projects in Taiwan's higher education.